On Cooperative Learning Process at SD N Kacangan 1, Sumberlawang, Sragen - Al Fath, Ayatullah Muhammadin; Pamungkas, Sri (Journal of Elementary School Education, 2024)
Family education is basic education for children before the child goes out into Family Education, Character, the wider world. The education provided by the family becomes a moral Cooperative Learning provision for children in life in society. Forming individual character cannotbe separated from the influence of family education. This research uses a qualitative method which is a research procedure that produces qualitative descriptive data in the form of written or spoken words from people and observed behavior and the implementation of this research was carried out at SDN Kacangan 1 with the data source being fifth grade students. The results of this research are 1) parents and teachers have a very important influence in the process of forming children's morals, because in an educational component there must be communication so that it is in harmony with the existing double standards. 2) students who have poor character will affect cognitive aspects and affective in the learning process in formal schools. The obstacles that parents often experience in the process of forming children's morals are peers and the school environment. With these things, it is hoped that parents will direct their teenagers more in positive ways. namely by being a good parental figure for their children. Introduce and teach religion to children from an early age.